Exploring EFL Undergraduate Students’ Experiences of Using QuillBot AI in Academic Writing: An Interpretive Phenomenological Study - Vania Zahrotun Nisa; Ahdi Riyono; Muh Syafei (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2026)
This study explored undergraduate EFL students’ lived experiences in using QuillBot AI during academic writing activities. The increasing use of artificial intelligence in language learning has encouraged students to utilize QuillBot not only as a technical writing aid but also as part of their academic revision practices. Using a qualitative approach with an interpretive phenomenological design, this study investigated how students perceived, negotiated, and responded to the use of QuillBot throughout the writing process. The participants consisted of seven undergraduate students from the English Education Study Program who had experience using QuillBot in academic writing tasks. Data were collected through semi-structured interviews and analyzed using thematic analysis. The findings revealed that students mainly used QuillBot during the revision stage to improve sentence structure, vocabulary variation, grammatical accuracy, and clarity of ideas after independently developing their drafts. Participants also carefully reviewed and modified AI-generated suggestions to ensure that the revisions remained aligned with their intended meaning and writing context. The study conceptualizes QuillBot as an “AI revision mediator” that supports revision practices while still allowing students to maintain authorship, evaluative judgment, and responsibility in their writing decisions. The study also contributes to discussions of AI-assisted writing by showing how students critically and reflectively engaged with AI during academic writing activities.